Caracterização hidrológica da bacia do córrego Samambaia, região da APA Carste de Lagoa Santa - MG - Isadora Pinto Coelho de Pinho Tavares (2020)
This study, carried out in the Samambaia stream area, located in the Lagoa Santa Karst APA - MG, aimed at the hydrological characterization of the basin and its anthropic interference in order to contribute to the improvement of water resources management in karst environments. The local geology is composed of recrystallized limestone rocks belonging to the Sete Lagoas Formation, with its members Pedro Leopoldo, represented by the occurrence of thin limestone interspersed with politic rocks, and Lagoa Santa, composed of pure calcarenites. This formation represents the main aquifer system in the region, which has typical structures of a well-developed karst. Overlying it there are pelitic and marl rocks of the Serra de Santa Helena Formation and, on top, the recent debris-lateritic and alluvial covers. Such carbonate terrain has typically karst structures (conduits, dolines, sinks) that control the mostly underground water flow. In the lower portion of the basin occurs the Sumidouro Lagoon, which began to empty from 2004. The study involved automated monitoring of spring and stream flow through five river stations throughout the hydrological year 2018- 2019, in addition to calculating the lagoon volumes through 4 Google Earth Pro images from 2003 on. Basin water inlet and outlet values, water and climate balance parameters and hydrological characterization of springs of this area were also calculated. Hypotheses that could explain the emptying of the Sumidouro Lagoon, exultory of the basin in question, were also suggested and analyzed. The results confirmed the classification as a typical karst basin, controlled mainly by the basin runoff (94%), with significant water outlets represented by catchments (1.35 million m³/year). The main water input comes from rain (24.18 million m³/year), followed by the contribution of the area's springs (4.12 million m³/year). In addition, the springs present rapid responses to rain events, not exceeding one day, with a large contribution of water from neighboring basins. Thus, as no major changes in rainfall and spring volume were found to justify the loss of water volume in the lagoon, it is suggested that the increased number of interferences in groundwater resources has caused a sink connection to drier conduits, which possibly caused an increase in its ability to drain the water contained in the lagoon, making it no longer full.